Fangyan Heshang: the Enlightenment Instructor of Jingxi Zhanran - CHI, Li-mei (Indogaku Bukkyōgaku kenkyū, 2006)
According to an inscription entitled “Xiao-shibei (The small stone monument), ” it is said that in the sixteenth year of the Kaiyuan era, Jingxi Zhanran came to Zhedong (the east part of Zhejiang) area to look for a Buddhist master. Three years later, before he eventually began to apprentice himself to Zuoxi Xuanlang, Zhanran met his enlightenment instructor from whom he had received instruction on Tiantai doctrines as well as some texts of Zhiguan (The cessation-and-contemplation). Due to the limited information on Fangyan Heshang, scholars only assumed that Fangyan was likely to be a disciple of Xuanlang. Not until 1999 did scholars, such as Xu Wenming of China and Kocho AKITA of Japan, begin to realize that Fangyan could be Fangyan Xuance, one of the disciples of Huineng—the sixth patriarch of the Southern Chan sect. Based on the assumption mentioned by the two scholars, this paper attempts first to outline the figure of Xuance, and then to review the possibility of identifying Fangyan Heshang with Xuance.